Pengembangan Kompetensi Pedagogik dan Profesional Guru PPKn pada Masa New Normal Covid 19 di Madrasah Tsanawiyah Negeri Se Kota Mataram - Septiana Andayani; M. Ismail; Muh. Zubair; Haryanto Haryanto (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2022)
Without neglecting other competencies, pedagogical competence and professional competence are absolute competencies possessed by an educator (teacher). This study aims to determine the efforts made by PPKn teachers in developing pedagogic competence and professional competence during the new normal covid-19. This study uses a qualitative approach with a descriptive type of research. Data collection techniques using interview and documentation techniques. The results showed that the efforts made by PPKn Madrasah Tsanawiyah Negeri teachers in Mataram City in developing pedagogic competencies and professional competencies were: (1) Attending education and training; (2) Participate in MGMP activities; (3) Participate in online workshops or seminars; (4) Seek and follow the development of information through electronic media, and; (5) Reading books or scientific journals.